Therapeutic communication skills of nurses in hospital - Masmuhul Khoir (Alta Dharma Publisher, 2020)
Nurses are the spearhead in health services that must be able to establish good relations with patients. An important skill in creating a good relationship with patients is therapeutic communication skills (TCS). The purpose of this study was to identify therapeutic communication skills of nurses in hospital. This research is a quantitative study using descriptive analysis method with a cross-sectional approach. Respondents of this study were 30 nurses who served in bangil hospital. The instrument used was questionnaire on the characteristics of the respondents and questionnaire on therapeutic communication skills. The data analysis used in this study is the chi-square test. The results of this study indicate 60.0% of respondents' therapeutic communication skills are good. The test results of the analysis between work experience and therapeutic communication skills showed a significance value of 0.015 (<0.05), meaning that there was a relationship between work experience and therapeutic communication skills. Whereas the results of the analysis between the therapeutic communication skills and characteristics of other respondents (gender, age, education, employment status, and marital status) show a value >0.05 means that there is no relationship. The therapeutic communication skills of nurses who are in hospital in the hospital are mostly good. Factors that can influence therapeutic communication skills are work experience. Means that the more often nurses conduct therapeutic communication, the better the ability of therapeutic communication. To improve therapeutic communication skills, continuous training is needed and training is provided along with regular and ongoing therapeutic communication practices.